Digital Translanguaging and Santri Cognition: Enhancing English Comprehension through Arabic-English Repertoires - Nur Aziz, Imam; Siddik, Nurah Abdul Wahid Abdullah (LP. Ma'arif Janggan Magetan, 2026)
This study investigates the integration of translanguaging within digital learning ecosystems to enhance English reading comprehension among bilingual Madrasah students, a context where Arabic religious literacy and academic English intersect. Using an integrated mixed-methods design, data were collected from 140 grade 11 students at two State Madrasahs in Indonesia. The quantitative phase employed a quasi-experimental design analyzed via ANCOVA, while the qualitative phase utilized screen-recording analysis and stimulated recall interviews. The results demonstrated that the translanguaging group significantly outperformed the monolingual group in reading comprehension (p<.001, n2p = .26). Qualitatively, the study revealed a